Aplikasi Waktu Pembukaan Okulasi dan Pemotongan Batang Bawah terhadap Pertumbuhan Awal Jeruk Siam Madu (Citrus nobilis L.) - Budi Siswanto; Praptiningsih Gamawati Adinurani; Sri Rahayu (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
Abstract— The percentage of failure to multiply "Siam madu" oranges by grafting in the rainy season is around 50 % to 80 %. The purpose of the study was to determine the interaction of rootstock pruning length and time of grafting plastic opening on the initial growth of  "Siam madu" oranges (Citrus nobilis L). The study used a factorial experiment based on a randomized block design (RAK). The first factor was the length of pruning (P) were, P1 = 5 cm above of patch eye with 0.5 stems, P2 = 5 cm above of patch eye, and P3 = 10 cm from the shoot. The second factor is the opening time of grafting plastic (B) were B1 = 25 days after grafting (DAG), B2 = 30 DAG and B3 = 35 DAG. Observation parameters included the percentage of grafting growth, time of shoot appearance, number of leaves, length of grafting shoots, and leaf area. The results showed that there was a significant interaction between the treatment of rootstock pruning length (P) and plastic opening time (B) to shoot appearance time, the number of leaves, shoot length, and leaf area. The best results of the combination variable treatment observed were achieved by the treatment of rootstock pruning length of 5 cm above of patch eye and opening time of grafting plastic 25 DAG (P2B1), namely shoot emergence time (30.20 days), shoot length 46 DAG (21.06 cm). In addition, the number of leaves was 46 DAG (10.66) and leaf area (225.96 mm2) Keywords—: grafting percentage growing;; root stock; scions; vegetative propagation